The adverse effect of gestational diabetes mellitus and hypertensive disorders of pregnancy on maternal–perinatal outcomes among singleton and twin pregnancies: a retrospective cohort study (2011–2019) - Nawsherwan; Zhiyi Liu; Zhang Le; Sumaira Mubarik; Sumaira Mubarik; Yanmei Sun; Shafaq Naeem; Hui Li (Frontiers in Endocrinology, 2023)
BackgroundGestational diabetes mellitus (GDM) and hypertensive disorders of pregnancy (HDP) are the predominant pregnancy complications among singleton and twin pregnancies worldwide. Our primary objective was to explore the adverse effect of GDM and HDP on maternal–perinatal outcomes compared with non-GDM and non-HDP in singleton and twin pregnancies. The secondary objective was to find the risk of adverse maternal–perinatal outcomes in twin pregnancies compared with singleton pregnancies complicated with GDM and HDP in Hubei, China.MethodsA tertiary hospital-based retrospective study was conducted at Wuhan University Renmin Hospital, Hubei Province, China, from 2011 to 2019. A chi-square test was used to determine the difference in adverse maternal–perinatal outcomes between singleton and twin pregnancies. A multiple binary logistic regression model and a joinpoint regression model were used to determine the association of GDM and HDP with adverse maternal–perinatal outcomes and GDM and HDP temporal trend among singleton and twin pregnancies.ResultsThe trend of HDP [average annual percentage change (AAPC) 15.1% (95% confidence interval (95%CI): 5.3, 25.7)] among singleton pregnancies and GDM [AAPC 50.4% (95%CI: 19.9, 88.7)] among twin pregnancies significantly increased from 2011 to 2019. After adjusting for confounding factors, GDM is associated with an increased risk of C-section (adjusted odds ratio (aOR), 1.5; 95%CI: 1.3, 1.6) and macrosomia (aOR, 1.3; 95%CI: 1.1, 1.6) in singleton and preterm birth (PTB) (aOR, 2.1; 95%CI: 1.2, 3.3) in twin pregnancies compared with non-GDM. HDP was associated with a higher risk of C-section, PTB, perinatal mortality, and low birth weight (LBW) in both singleton and twin pregnancies compared with the non-HDP. Compared with singleton pregnancies complicated with GDM and HDP, twin pregnancies showed higher odds of C-section [(aOR, 1.7; 95%CI: 1.1, 2.7), (aOR, 4.6; 95%CI: 2.5, 8.7), respectively], PTB [(aOR, 22.9; 95%CI: 14.1, 37.3), (aOR, 8.1; 95%CI: 5.3, 12.3), respectively], LBW [(aOR, 12.1; 95%CI: 8.2, 18.1), (aOR, 5.1; 95%CI: 3.6, 7.4), respectively], and low Apgar score [(aOR, 8.2; 95%CI: 4.4, 15.1), (aOR, 3.8; 95%CI: 2.4, 5.8), respectively] complicated with GDM and HDP.ConclusionIn conclusion, GDM showed an increased risk of a few adverse maternal–perinatal outcomes and HDP is associated with a higher risk of several adverse maternal–perinatal outcomes in singleton and twin pregnancies compared to non-GDM and non-HDP. Moreover, twin pregnancies complicated with GDM and HDP showed higher odds of adverse maternal–neonatal outcomes compared with singleton pregnancies complicated with GDM and HDP.